1996
DOI: 10.1136/mp.49.3.m151
|View full text |Cite
|
Sign up to set email alerts
|

Genes mediating programmed cell death: an immunohistochemical study of bcl-2, c-myc and p53 expression in colorectal neoplasia

Abstract: Aims-To describe the expression of three genes involved in the regulation of cell proliferation and programmed cell death (apoptosis) in normal, dysplastic and malignant large bowel epithelium, and to relate any alterations to important biological and clinical variables. Methods-Immunohistochemistry was used to assess bcl-2, c-myc and p53 gene expression in 70 colorectal carcinomas, 36 adenomas and three samples of normal mucosa. Results-Bcl-2 and c-myc protein were detected in all samples of normal mucosa and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
22
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 37 publications
5
22
1
Order By: Relevance
“…Hague et al [28] and Sinicrope et al [14] reported bcl-2 staining in over 60% of colorectal carcinomas. Our data, which have already been reported [17], are in agreement with those of Scott et al [29] and Kaklamanis et al [30] and indicate that relative to colorectal adenomas, colorectal carcinomas show a reduction in bcl-2 expression. Given the function of bcl-2 as apoptosis suppressor and the decreased rate of apoptosis in colorectal carcinomas this paradox is not easy to explain.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Hague et al [28] and Sinicrope et al [14] reported bcl-2 staining in over 60% of colorectal carcinomas. Our data, which have already been reported [17], are in agreement with those of Scott et al [29] and Kaklamanis et al [30] and indicate that relative to colorectal adenomas, colorectal carcinomas show a reduction in bcl-2 expression. Given the function of bcl-2 as apoptosis suppressor and the decreased rate of apoptosis in colorectal carcinomas this paradox is not easy to explain.…”
Section: Discussionsupporting
confidence: 83%
“…It has become clear, however, that the regulation of apoptosis is complex and involves not only bcl-2 but also a variety of other members of this gene family [11,12], in addition to other regulating genes, including p53 and c-myc. This might imply that carcinomas acquire other genetic lesions, which render bcl-2 redundant [29]. Bcl-2 expression was not correlated with p53 expression, as reported previously [29].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Resistance of colonocytes to apoptosis may allow hyperproliferation, accumulation of oncogenic mutations and prevent deletion of malignant cells by chemotherapeutic agents. Abnormal expression of the apoptosis-related genes p53 and bcl-2 has been reported in both benign and malignant colon tumours (Sinicrope et al, 1995;Scott et al, 1996), however other molecular mediators of resistance to apoptosis remain to be identified.…”
mentioning
confidence: 99%